Aligning the contents of curriculum of undergraduate medical education in Bangladesh with health related targets of Sustainable Development Goals (SDG). (Bangladesh Journal of Medical Education, 2020)
Abstract Introduction: This descriptive type of cross sectional study was conducted to assess teachers’ views regarding the alignment of contents of curriculum of undergraduate medical education in Bangladesh with the health related targets of Sustainable Development Goals.Methods: The study was conducted during the period of July 2018 to June 2019. The study used standardized pre-tested instruments. Convenience sampling technique was employed to include 04 public and 04 private medical colleges, of which 05 were located in Dhaka city and 03 were located outside Dhaka city. Data were collected from 123 faculty members by using self-administered semi-structured questionnaire and from 25 Key informants by using in-depth Interview schedule. Data entry and analysis was done using SPSS 19.0.Results: Among 123 medical teachers 84(68.3%) opined inadequacy of contents about neglected tropical diseases, 97(78.9%) about road traffic accidents, 103(83.7%) about narcotic drug abuse, 93(75.6%) about universal health coverage, 108(87.8%) about sexual health care services, 97(78.9%) viewed about tobacco control and 116(94.3%) about early warning about national and global health risks.Conclusion: To achieve the health related targets of SDG, the curriculum of undergraduate medical education should be reviewed with inclusion of relevant contents which will help students to achieve relevant competencies of SDGs.Bangladesh Journal of Medical Education Vol.11(2) 2020: 21-26